Excavatability classification of rocks around haroglu mountain in Northeast of Baskil in Elazig according to engineering geology properties - Kılıç, Ebubekir (My University, 2021)
Abstract Knowledge of the geology of the ground to be excavated in surface mines and foundations, especially in civil engineering works, is very important to decide on the appropriate excavation method and equipment and ensure human and equipment safety with time and cost savings. For this purpose, the engineering geological properties and excavatability classification of rocks around the Haroglu Mountain located in the northeast of Baskil in Elazig were studied. The research started with a desktop study and then continued with a walkover, the determination, and mapping of lithostratigraphic units outcropping in this study area. Yuksekova Formation, Kuscular Formation, Seske Formation, Kirkgecit Formation, and surficial deposits are the lithostratigraphic units in order of occurrence from old to young. Yuksekova Formation, the oldest unit between them, makes up of a group of plutonic, hypabyssal, volcanic, and pyroclastic rocks. After Yuksekova Formation occurs which is magmatic, the sedimentary sequence begins to form with Middle Paleocene-aged rocks. Sedimentary rocks are divided into three formations according to their stratigraphic properties. In order of occurrence from old to young, these sedimentary formations are composed of Kuscular conglomerate, Seske Formation, Kirkgecit Formation. Also, surficial deposits as the youngest unit are formed occasionally over other formations. The structural geological properties of the formations, one of the most important parameters of the excavability, were mapped. The set number, roughness, magnitude of the angle of dip, azimuth of strike or dip of discontinuities or joints, and the block volume are the significant parameters that are influenced excavatability. The azimuths of strikes of discontinuities were measured and carried out the rose diagrams from them. As a result of these measurements, the discontinuities or fractures in Yuksekova Formation have been usually found in the azimuth of a strike having NNE and a 45-90 SW of angle and azimuth of dip. It was determined that the orientation of K60W of excavation is the orientation of a very favorable excavation based on the discontinuity attitudes in the study area. It was established that the orientation of a very unfavorable excavation also is in the azimuth of the strike of fracture, namely N30E. Excavatability of the rocks was determined by assessment of lower and upper discontinuity spacing index and point load strength values. Yuksekova Formation requires methods that can be excavated from very hard to extremely hard ripping (D 9)–blasting by taking into consideration formations exposed in the study area. Kuscular Formation can be excavated by methods of easy ripping (D 6-D 7) to hard ripping (D 8) and Seske Formation also easy ripping (D 6-D 7)-very hard ripping (D 9). Kirkgecit Formation has the capabilities of being excavated by methods of hard digging (CAT 245) to very hard ripping (D 9). As a result of this study, the order of excavatability as the rocks from hard to easy can be expressed as the micro-diorite, granite, andesite, and diorite of Yuksekova Formation, the conglomerate of Kırkgecit Formation and the conglomerate of Kuscular Formation. Finally, the limestone and shale of Kirkgecit Formation would be also excavated the easiest respectively. Additionally, it has been revealed that surficial deposits can be also excavated optimally by easy digging method.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Blasting; Digging; Discontinuity spacing index; Excavatability; Formation; Ripping